Purchasing and up-scaling of the privatized advisory services: An innovation perspective on privatized soil testing in Africa. Issue 3 (26th May 2020) - Malima, Gabriel; Eshetie, Saba; Rahaman, Abdulai; Mrosso, Pastory; Witteveen, Loes
ABSTRACT: As the trend of privatizing agricultural advisory services grows in developing countries, the need for the systematic thinking in innovation development is of interest for private companies that are trying to introduce various technologies in the agriculture sector. We explored the factors that affect the purchasing and upscaling of the privatized agricultural advisory services. We used a mobile soil testing service offered by a private company in Kenya as a case study. Additionally, we conducted minor explorations in Ethiopia, Ghana, and Tanzania. Our study found out that, while the service with its financial arrangement seems to be accepted by farmers, the social organization of system institutions is complex because not only technical factors but also social factors influenced adoption of the service. The study is an exemplifying case of the relevance of modeling innovations as complex configurations in a dynamic system of diverse actors in a community.